The Effect of the Multisensory Method on Beginning Reading Skills of First Grade Dyslexic Students at XYZ Inclusive Elementary School - Andriany, Anissa Rizky; Pandia, Weny Savitry S. (Kepompong Children Centre Journal, 2024)
This study aims to examine the effect on the ability multisensory method with the previous reading of dyslexia students grade one. This experimental study conducted on a group by using one group pre-test - post-test design. Subjects numbered 5 students who were selected using the instrument read the beginning. The fifth subject has the ability to read starters are in the poor category. Data collection instruments such as observation sheets pre-test and post-test. Data analysis technique used is descriptive quantitative and qualitative descriptions. The results showed there were differences in the ability to read the beginning of dyslexic students grade one before and after treatment with multisensory method (Assymp. Sig. .043 <.05). These results further reinforced the results of Wilcoxon Signed Ranks Test which shows there is a difference value of 21.800 pre-test and post-test score of 38.200, as well as an increase of 16,400. This improvement can also be seen from the observation in every meeting when given treatment.